Stages in the degeneration of flight ability and their interspecific comparisons in the genus Synuchus (Coleoptera: Carabidae) in Japan - Takashi SHIMIZU; Kôhei KUBOTA; Hiroshi IKEDA (European Journal of Entomology)
The degeneration in flight ability in beetles has rarely been studied in detail with regard to the polymorphism of flight traits within species. However, intraspecific diversity in flight traits means that the flight ability of species is in the process of degenerating, which could provide important insights into how flight ability in beetles degenerates. In this study, the flight muscle and hind wings of the genus Synuchus in Japan were studied, which revealed the morphological status of flight traits in 21 species of Synuchus. Several species in this genus were found to show intraspecific polymorphisms in the states of the flight muscle and hind wings, and in particular, the very high diversity of different types of hind wings. These results indicate that this genus contains a mixture of species at various stages in the degeneration of the ability to fly.